(untitled) (Architecture Image Studies, 2025)
This study analyzes the impact of Universal Design for Learning (UDL) in inclusive education contexts, focusing on student participation and academic achievement. Using a sequential explanatory mixed-methods approach, quantitative instruments (participation scales and standardized tests) and qualitative tools (interviews and classroom observations) were applied to teachers and students from three Ecuadorian educational institutions. The results show significant improvements in active student engagement and academic performance when UDL-based strategies are implemented. Additionally, key enabling conditions were identified, such as pedagogical leadership, teacher training, and the use of accessible technologies. The study concludes that UDL not only benefits students with special educational needs but also enhances the overall quality and equity of learning for the entire school community. The article ends with recommendations for teachers, school administrators, and education policymakers.